(untitled) (El-Wahat Journal for Research and Studies, 2026)
This study explores how marginalized childhood is culturally modeled in visual media through an analysis of three films: Anastasia, Lilo & Stitch, and Belle and Sebastian. Centering on children who are orphaned, abandoned, or socially excluded, the research investigates how these characters are transformed into empowered figures capable of redefining their identity and place in the world. By employing semiotic analysis and postmodern interpretive frameworks, the study uncovers how these films construct alternative visions of family, belonging, and emotional connection—often shifting attachment from traditional family structures to non-human or unfamiliar figures. Ultimately, the paper highlights how visual media not only portrays childhood marginalization but also reimagines it as a space for resistance, transformation, and cultural meaning-making.